Omega-3 Fatty Acids Supplementation Improve Nutritional Status and Inflammatory Response in Patients With Lung Cancer: A Randomized Clinical Trial - Cheng, Mingjin; Zhang, Shengqiang; Ning, Chengdong; Huo, Qianlun (Frontiers in Nutrition, 2021)
Background and Aims: Clinical studies have reported positive results with omega-3 supplements in patients with cancer. This study aimed to evaluate the efficacy of omega-3 fatty acid supplementation in improving the nutritional status and inflammatory markers of patients with lung cancer. Methods: In a randomized, double-blind, parallel design trial, 60 patients with lung cancer at nutritional status/risk based on the Nutrition Risk Screening 2002 were randomized to be allocated to two study groups, receiving omega-3 fatty acid supplements [eicosapentaenoic acid (EPA) 1.6 g and docosahexaenoic acid (DHA) 0.8 g] or placebo for 12 weeks. Anthropometric measurements [weight, body mass index (BMI), the circumference of the upper arm, and skinfold thickness of triceps], nutrition-based laboratory indices (hemoglobin, albumin, triglyceride, and cholesterol), and inflammatory markers [C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), and interleukin 6 (IL-6)] were measured before and after the intervention as study outcomes. Results: No significant difference between the two study groups was observed regarding basic characteristics and study outcomes. Compared with placebo group, omega-3 fatty acid supplementation group showed significant higher weight (66.71 ± 9.17 vs. 61.33 ± 8.03, p = 0.021), albumin (4.74 ± 0.80 vs. 4.21 ± 0.77, p = 0.013), and triglyceride (130.90 ± 25.17 vs. 119.07 ± 14.44, p = 0.032). Inflammatory markers were significantly reduced in omega-3 group compared to placebo (CRP 1.42 ± 0.63 vs. 3.00 ± 1.05, p = 0.001 and TNF-α 1.92 ± 0.65 vs. 4.24 ± 1.19, p = 0.001). No significant difference was observed between the two study groups regarding changes in BMI, the circumference of the upper arm, skinfold thickness of triceps, triglyceride, cholesterol, and IL-6 (p > 0.05). Conclusions: Omega-3 fatty acid supplementation can improve nutritional status and suppress the systemic inflammatory response in patients with lung cancer. Clinical Trial Registration:www.socialscienceregistry.org, identifier: AEARCTR-0007165.